Peran Kepuasan Kerja Dipengaruhi Gaji, Stabilitas Pekerjaan, Pengayaan Pekerjaan, dan Lingkungan Kerja terhadap Komitmen Karyawan - Dihin Septyanto; Fitriyani Khasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Employee commitment is an important factor for the success of industrial companies in Tangerang City, especially in the tire production industry sector, because committed employees tend to increase job satisfaction, productivity, and profitability. This study aims to determine the effect of salary, job stability, job enrichment, and work environment on job satisfaction and employee commitment. The method in this study is quantitative, with a non-probability sampling method and a purposive sampling technique of 150 male employee respondents in the mixing center department at XYZ company in Tangerang City who have worked for at least 2 years. The results of data analysis using Partial Least Square - Structural Equation Modeling (PLS-SEM) show that salary, job stability, job enrichment, and work environment have a positive effect on job satisfaction and employee commitment. This research encourages companies to focus more on job satisfaction and employee commitment. It is expected that future researchers will add other variables that may be influential, such as organizational culture, leadership style, and employee performance to broaden their understanding of the factors that influence job satisfaction and employee commitment.